The language style in the Korean language tourism advertising slogans on a YouTube channel - Vinka Tiara Aliyya Nurfatwa; Rudi Adi Nugroho; Didin Samsudin (Universitas Pendidikan Indonesia (UPI), 2023)
The language style is prominently showcased within advertising slogans. They can deliver meaningful messages by captivating the viewers. Therefore, this research discusses the language style and the semantic meaning contained in the Korean language tourism advertising slogans on a YouTube channel. This research aims to find out how language style and semantic meaning are manifested in Korean tourism advertising slogans. The research object was the Korean tourism advertisement based on the main components of tourism aired through YouTube channels in 2014-2021. The research variables were the language and semantic meaning manifested on the Korean tourism advertising slogans. This research used a qualitative descriptive method through observation technique to obtain the data, particularly involving listening and note-taking techniques. The data were analyzed by using interactive and referential techniques. This research used Jang and Kim’s language style theory and Leech’s semantic meaning theory. The results showed that there were twelve types of language styles found in Korean language tourism advertising slogans. The most common language style was personification. The purpose of personification was to make the advertising slogan much more live and more beautiful so that it can be easier to remember. Moreover, the results revealed that there were 25 connotative meanings and 25 denotative meanings in the Korean tourism advertising slogans. Denotative meaning could convince consumers with the actual facts. Connotative could attract the consumers’ attention with eloquent words without reducing the value of the products offered.